Simulation Analysis of the System Reliability of Cylinder Sine Oscillating Tooth Transmission - Yuan Xinmei; Zeng Yunyun; Zhou Sizhu (Jixie chuandong, 2015)
In view of the problem that the conventional analysis method cannot directly solve reliability problem of the complex cylinder sine oscillating tooth transmission system,a simulation method based on minimal cut sets of fault tree is proposed,which can solves system reliability.According to the structural characteristics of cylinder sine oscillating tooth transmission,the function block diagram of the system is given and the fault tree of the system is built.The minimal cut sets of the fault tree are acquired,and the cumulative failure probability and the probability density are calculated.Different types life distribution function of the system are fitted out.The life distribution function is determined preliminarily based on the principle of minimum residual sum of squared,and the K-S hypothesis testing is carried out for the life distribution function,which ultimately determine life distribution function of cylinder sine oscillating tooth transmission is Weibull distribution.The weak links of cylinder sine oscillating tooth transmission system are determined by analysis of model importance.